A real Cinderella - Rhoades, Nina, 1863-1940; Withington, Elizabeth R. (Elizabeth Rupp), 1883-1962 (Salt Lake City, UT : Project Gutenberg, 2024)
"A Real Cinderella" by Nina Rhoades is a children's novel written in the early 20th century. The story follows a young girl named Gretel Schiller, who, despite her humble circumstances and lack of familial support, dreams of a more magical life reminiscent of the classic fairy tale Cinderella. The novel explores themes of hope, longing, and the transformative power of music as Gretel navigates her daily life filled with chores, moments of joy, and the wish to experience "fairy-land." The opening of the book introduces us to Gretel, an orphaned girl living with the Marsh family, who is often treated more like a servant than a relative. Through her interactions with Miss Ada Marsh and her half-heartedly welcoming home life, Gretel dreams of attending opera performances, which she sees as gateways to a beautiful world where she might find happiness. As she grapples with feelings of inadequacy, neglect, and her aspirations, she discovers a ticket to an opera, igniting her desire to escape her reality and seek the enchantment she believes lies beyond her grasp. The initial chapters set the stage for Gretel's journey through self-discovery, the significance of music in her life, and the contrasting worlds of hope and despair she experiences. (This is an automatically generated summary.)
Release date is 2024-12-15
Susan E., David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Orphans -- Juvenile fiction; Siblings -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Girls -- Juvenile fiction